2000
DOI: 10.1155/2000/389361
|View full text |Cite
|
Sign up to set email alerts
|

New Algorithms Based on the Voronoi Diagram Applied in a Pilot Study on Normal Mucosa and Carcinomas

Abstract: An adequate reproducibility in the description of tissue architecture is still a challenge to diagnostic pathology, sometimes with unfortunate prognostic implications. To assess a possible diagnostic and prognostic value of quantitiative tissue architecture analysis, structural features based on the Voronoi Diagram (VD) and its subgraphs were developed and tested.A series of 27 structural features were developed and tested in a pilot study of 30 cases of prostate cancer, 10 cases of cervical carcinomas, 8 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 43 publications
2
43
0
Order By: Relevance
“…In the present paper, we demonstrate that, in particular, the invasive front of OSCC contains morphologic information with high prognostic value. The results in the present study are consistent with our previous findings in a pilot study, in which we found that graph theory-based quantitation of tissue architecture was well suited for prognostication of several types of carcinomas (Sudbø et al, 2000).…”
Section: Sudbø Et Alsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present paper, we demonstrate that, in particular, the invasive front of OSCC contains morphologic information with high prognostic value. The results in the present study are consistent with our previous findings in a pilot study, in which we found that graph theory-based quantitation of tissue architecture was well suited for prognostication of several types of carcinomas (Sudbø et al, 2000).…”
Section: Sudbø Et Alsupporting
confidence: 92%
“…Alignment of the fields of view relied on the mechanical precision of the microscope stage. After compiling 36 to 81 fields of view, areas of interest were digitally defined as closed contours using a previously described algorithm (Sudbø et al, 2000). Only cellular elements within the digitally defined areas were included in the computations (Fig.…”
Section: Sudbø Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Accuracy of the model is stable over much of the parameter range, with lower accuracy only occurring where lambda forces few to no features to be included in the model. Dundar et al, 2011Dundar et al, , 2010Esgiar et al, 2002;Farjam et al, 2007;Fatima et al, 2014;Glotsos et al, 2008;Gunduz et al, 2004;Gupta et al, 2001;Hall et al, 2008;Huang and Lai, 2010;Huang and Lee, 2009;Jafari-Khouzani and Soltanian-Zadeh, 2003;Monaco and Tomaszewski, 2008;Kong et al, 2007;Kwak et al, 2011;Land et al, 2008;Lessmann et al, 2007;Meng et al, 2010;Naik et al, 2008Naik et al, , 2007Ozolek et al, 2014;Petushi et al, 2006;Qureshi et al, 2008Qureshi et al, , 2007Sboner et al, 2003;Schnorrenberg et al, 1997;Sertel et al, 2010;Sparks and Madabhushi, 2013;Sudbø et al, 2000;Tabesh and Teverovskiy, 2006;Tabesh et al, 2007Tabesh et al, , 2005Tahir and Bouridane, 2006;Tasoulis et al, 2003;Teverovskiy et al, 2004;Thiran and Macq, 1996;Tsai et al, 2009;Xu et al 2014aXu et al , 2014bYang et al, 2009). These approache...…”
Section: Discussionmentioning
confidence: 99%
“…Even before WSI was practical, researchers captured a single frame of an entire slide using a standard microscope creating a subset of the image for computational analysis (Adiga et al, 2006;Aiad et al, 2009;Altunbay et al, 2010;Baak et al, 1981;Brook et al, 2007;Esgiar et al, 2002Esgiar et al, , 2002Farjam et al, 2007;Fatima et al, 2014;Glotsos et al, 2008;Gunduz et al, 2004;Gupta et al, 2001;Hall et al, 2008;Huang and Lai, 2010;Huang and Lee, 2009;Jafari-Khouzani and Soltanian-Zadeh, 2003;Kong et al, 2007;Land et al, 2008;Lessmann et al, 2007;Meng et al, 2010;Ozolek et al, 2014;Qureshi et al, 2008Qureshi et al, , 2007Sboner et al, 2003;Schnorrenberg et al, 1997;Sudbø et al, 2000;Tahir and Bouridane, 2006;Tasoulis et al, 2003;Thiran and Macq, 1996;Tsai et al, 2009). For many researchers doing pathology image analysis today, this is still the best option, either because they do not have access to a WSI system, or because they can capture data not possible with a WSI system, such as confocal microscopy images.…”
Section: Image Subsetting Methodsmentioning
confidence: 99%